Full Film, Boundary Lubrication and Tribochemistry in Steel Circular Contacts Lubricated with Glycerol - Habchi, W. (2015)
In this article, the lubricating properties of pure glycerol are investigated under both mild and severe EHL regimes. Amazingly low friction coefficients (about 0.01) are reported by experiments in thick film regimes compared to traditional base oils. EHL calculations of film thickness and friction (including thermal effects) predict friction coefficients that are twice those actually found for glycerol. Chemical analysis of glycerol before and after the friction tests were performed by NMR and Karl Fischer methods, and they reveal that water is produced by tribochemical reaction as well as other species like aldehydes. This finding is in agreement with a corrosion pattern observed inside the wear scars of the steel samples. This study provides an explanation to the anomalously low friction observed in the thick film regime. In fact, water produced in the lubricant decreases traction forces due to the drastic decrease of the viscosity of glycerol with water addition.